ARTIKEL REVIEW : UJI AKTIVITAS FARMAKOLOGI ROYAL JELLY - Dikdik Caesar Barkah; Dyanita Irene Susilo Putri; Fera Anggraeni; Lutfiah Nur Fitria; Neni Sri Gunarti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Beekeeping is the science and art of prolonging and maintaining health by using products obtained from honeycombs, such as honey, bee bread, bee pollen, propolis, and royal jelly. Currently, many studies are devoted to investigating the directed health benefits and fermacological properties of bee products due to their properties. One of the studies conducted was research on royal jelly. Royal jelly is widely used as a dietary nutritional complex to help combat various chronic health conditions, besides, it is one of the beneficial medicines for humans in both traditional and modern medicine. The aim of this research is that many fermacological activities such as antibacterial, antitumor, antiallergic, anti-inflammatory, and immunomodulatory effects are associated with it. Royal jelly consists of water (50%-60%), protein (18%), carbonate (15%), ipid (3%-6%), mineral salts (1.5%), and vitamins. Based on modern spectrometric analysis, about 185 organic compounds have been detected in royal jelly.